Analogs of the carotane antibiotic fulvoferruginin from submerged cultures of a Thai Marasmius sp. - Sandargo, Birthe; Kaysan, Leon; Teponno, Rémy B.; Richter, Christian; Thongbai, Benjarong; Surup, Frank; Stadler, Marc (Beilstein Journal of Organic Chemistry, 2021)
A recent find of a Marasmius species in Northern Thailand led to the isolation of five unprecedented derivatives of the carotane antibiotic fulvoferruginin (1), fulvoferruginins B–F (2–6). The structures of these sesquiterpenoids were elucidated using HRESIMS, 1D and 2D NMR, as well as CD spectroscopy. Assessing the bioactivity, fulvoferruginin emerged as a potent cytotoxic agent of potential pharmaceutical interest.
Keywords: antibiotics; Basidiomycota; carotane; fulvoferruginin; Marasmius; sesquiterpenoid

(untitled) - Wijayawardene, N. N.; Hyde, K. D.; Al-Ani, L. K. T.; Tedersoo, L.; Haelewaters, D.; Rajeshkumar, K. C.; Zhao, R. L.; Aptroot, A.; Leontyev, D. V.; Saxena, R. K.; Tokarev, Y. S.; Dai, D. Q.; et al. (Mycosphere, 2020)

(untitled) - Matheny, P. B.; Curtis, J. M.; Hofstetter, V.; Aime, M. C.; Moncalvo, J.-M.; Ge, Z.-W.; Yang, Z.-L.; Slot, J. C.; Ammirati, J. F.; Baroni, T. J.; Bougher, N. L.; Hughes, K. W.; et al. (Mycologia, 2006)

(untitled) - Oliveira, J. J. S.; Vargas-Isla, R.; Cabral, T. S.; Rodrigues, D. P.; Ishikawa, N. K. (Mycol. Prog., 2019)

(untitled) - Meng, J.; Li, Y.-Y.; Ou, Y.-X.; Song, L.-F.; Lu, C.-H.; Shen, Y.-M. (Mycology, 2011)

(untitled) - Ayer, W. A.; Craw, P. (Can. J. Chem., 1989)

(untitled) - Liermann, J. C.; Thines, E.; Opatz, T.; Anke, H. (J. Nat. Prod., 2012)

(untitled) - Fabian, K.; Anke, T.; Sterner, O. (Z. Naturforsch., C: J. Biosci., 1999)

(untitled) - Klein, J.; Anke, T.; Sheldrick, W. S.; Bross, M.; Steffan, B.; Steglich, W. (Z. Naturforsch., C: J. Biosci., 1990)

(untitled) - Huneck, S.; Cameron, A. F.; Connolly, J. D.; McLaren, M.; Rycroft, D. S. (Tetrahedron Lett., 1982)

(untitled) - Huo, G. H.; Wu, T. F.; Peng, W. W.; Hu, D. M.; Li, Z. M.; Huo, D. (Chem. Nat. Compd., 2019)

(untitled) - Wannathes, N.; Desjardin, D. E.; Hyde, K. D.; Perry, B. A.; Lumyong, S. (Fungal Divers., 2009)

(untitled) - Aime, M. C.; Miller, A. N.; Aoki, T.; Bensch, K.; Cai, L.; Crous, P. W.; Hawksworth, D. L.; Hyde, K. D.; Kirk, P. M.; Lücking, R.; May, T. W.; Malosso, E.; et al. (IMA Fungus, 2021)

(untitled) - Sandargo, B.; Michehl, M.; Praditya, D.; Steinmann, E.; Stadler, M.; Surup, F. (Org. Lett., 2019)

(untitled) - Surup, F.; Hennicke, F.; Sella, N.; Stroot, M.; Bernecker, S.; Pfütze, S.; Stadler, M.; Rühl, M. (Beilstein J. Org. Chem., 2019)

(untitled) - Sandargo, B.; Michehl, M.; Stadler, M.; Surup, F. (J. Nat. Prod., 2020)